On the Role of Scalar Fields in the Evolutionary Development of the Early Universe - Teryan, H. K.
In most constructions of the inflationary regime of the development of the Universe, the presence of a specific scalar field (inflaton) is assumed, which contributes to the expansion of space at an enormous pace. In the present work, we study the dynamics of a conformally bound scalar field for the de Sitter case, in the presence of a closer connection between the potential and the space curvature R.
Keywords: Physics